Colocated and Distributed Switch-and-Stay Combining: Optimality Under Switching Rate Constraints - Jataprolu, Manjunath Kashyap; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2013)
Switch-and-stay combining (SSC) is a low-complexity alternative to selection combining (SC) in dual diversity systems. These diversity systems can either be the conventional colocated diversity setups, where two antennas are available at the receiver, or the cooperative diversity systems, where two relays assist one transmitter-receiver pair. In SSC, a single diversity branch (i.e., a single antenna or a single relay) is activated and remains active as long as the corresponding channel is sufficiently strong, regardless of the quality of the other branch. Thereby, the switching threshold determines both the bit error rate (BER) and the switching rate, which are defined as the number of times per second a branch switching occurs. Since high switching rates are not preferred in practice, in this paper, we optimize the switching threshold of SSC to minimize the BER under a constraint on the switching rate. To this end, we derive approximate closed-form solutions for the optimization problem for both the colocated and the distributed antenna case. These solutions are shown to achieve close-to-optimal performance through computer simulations.<br
Keywords: cooperative communication; diversity reception; error statistics; optimisation; relay networks (telecommunication); telecommunication switching